Double Identity Representation of Chinese Shrines in Phuket Muang District - Chanasakun, Panuwat (Journal of International Studies, Prince of Songkla University, 2017)
“Double Identity Representation of Chinese Shrines in Phuket District” has the main objectives o study the adaptations of Chinese culture in the context of Thai society through Chinese shrine in Muang Phuket District and to comprehend the phenomena of double identity which represent through Chinese shrine in Muang Phuket District. The in-depth interviews and Participant Observation of the Qualitative research methods were used in this study. The Chinese shrines are part of maintaining and expressing Chinese culture. Chinese shrines and Chinese-Thai were adopted with Thai culture and belief. This phenomenon is presented by the double identity form. Chinese Shrines are the expression of the Hybridity of culture and are a central of Chinese culture and double identity through the forms of art, religious activities and figures of god. Chinese shrines are involved with various organizations; both public and private sectors, and have a role to Thai society through the public benefit activities and social welfares. The double identity representation is development of a good relationship between Thai ethnic and Chinese cultural groups.